Efficacy and Safety of Xuebijing Injection Combined With Ulinastatin as Adjunctive Therapy on Sepsis: A Systematic Review and Meta-Analysis - Chen, Guochao; Gao, Yanyan; Jiang, Yue; Yang, Fei; Li, Shuangshuang; Tan, Di; Ma, Qun (Frontiers in Pharmacology, 2018)
Background: Xuebijing injection (XBJ), transforming from Xuefuzhuyu decoction, is the only Chinese medicine injection approved for sepsis. XBJ and ulinastatin (UTI) combination therapy is supposed to be beneficial for sepsis patients. To fill the gap between the lack of evidence for the efficacy of combination therapy and its increasing application among patients, an extensive meta-analysis was performed. Methods: Eight databases were searched to identify randomized controlled trials (RCTs) comparing XBJ plus UTI with UTI alone in treating sepsis from inception to February 5, 2018. Data extraction and methodological quality assessment of the included RCTs were implemented by two investigators independently. All data were synthesized and analyzed utilizing Review Manager 5.3. Results: 17 RCTs with a total of 1247 participants corresponded with the inclusion criteria of our study. The findings reflected that in comparison to single UTI, XBJ and UTI combination therapy could significantly lower 28-day mortality (RR = 0.54, 95% CI [0.39, 0.73], P < 0.0001), shorten duration of mechanical ventilation (SMD = -1.13, 95% CI [-1.30, -0.95], P < 0.00001), reduce length of ICU stay (SMD = -0.84, 95% CI [-1.00, -0.67], P < 0.00001), and decrease APACHE II score (SMD = -1.09, 95% CI [-1.49, -0.69], P < 0.00001). Additionally, XBJ plus UTI had superiority over single UTI in lowering PCT levels (SMD = -1.61, 95% CI [-2.23, -0.98], P < 0.00001), and improving inflammatory cytokines－IL-6 and TNF-ɑ levels (SMD = -1.45, 95% CI [-1.71, -1.19], P < 0.00001; SMD = -1.11, 95% CI [-1.42, -0.80], P < 0.00001). Moreover, CRP, hs-CRP, and LPS levels were remarkably reduced by XBJ plus UTI compared with UTI alone (SMD = -1.50, 95% CI [-2.00, -1.00], P < 0.00001; SMD = -1.31, 95% CI [-1.70, -0.93], P < 0.00001; SMD = -1.17, 95% CI [-1.42, -0.92], P < 0.00001). 3 studies involving 14 patients reported the occurrences of adverse events. Conclusions: Comparing with UTI alone, XBJ and UTI combination therapy appeared to be more effective for sepsis. However, owing to the limitations of this meta-analysis, additional RCTs with higher-quality and more rigorous design are needed to confirm our findings.